Sounding prose music in the 17th-century Dutch novel. - VELDHORST, NATASCHA (Anthem Impact., 2022)
This book is about the presence of music in novels. More specifically, about music in the early modern novel, with an emphasis on seventeenth-century prose from The Netherlands. The essay provides a concise and an accessible introduction into the subject and presents an overview of this compelling new research area.